Islamisation and its opponents in Java : a political, social, cultural and religious history, c. 1930 to the present - Ricklefs, M. C. (Merle Calvin) (UPCC book collections on Project MUSE., 2012)
The Javanese -- one of the largest ethnic groups in the Islamic world -- were once mostly "nominal Muslims", with pious believers a minority and the majority seemingly resistant to Islam's call for greater piety. Over the tumultuous period analyzed here -- from colonial rule through japanese occupation and Revolution to the chaotic democracy of the Sukarno period, the Soeharto regime's aspirant totalitarianism and the democratic period since -- the society has changed profundly to become an extraordinary example of the rising religiosity that marks the modern age. Islamisation and Its Opponents in Java draws on a formidable body of sources, including interviews, archival documents and a vast range of published material, to situate the Javanese religious experience from the 1930s to the present day in its local political, social, cultural and religious settings. The concluding part of the author's monumental three-volume series assessing more than six centuries of the on-going Islamisation of the Javanese, the study has considerable relevance for much wider contexts. Beliefs, or disbeliefs, about the supernatural are important in all societies, and the final section of the book, which considers the significance of Java's religious history in global contexts, shows how it exemplifies a profound contest of values in the universal human search for a better life.